Broiler Microbiological and Histological Response to Diets Varying in Sodium and Calcium Butyrate - Mayada Saeed Sultan (Zien Journals, 2023)
The aim of the study was to determine the effect of supplementing broiler diets with different levels of sodium and calcium butyrate on certain histological and microbial traits. This study was conducted in the poultry field of the Department of Animal Production at the College of Agricultural Engineering Sciences / University of Baghdad (Baghdad, Iraq) during November - December (2020) in a total of 308 one-day-old chicken utilized in the study, and each treatment had three replicates consisting of 10 chicks each. Duodenal villi height increased significantly (p <0.05) for treatments T2, T3, T4, and T5, villi thickness increased significantly (p><0.05) for treatment T3, and crypt depth increased significantly (p><0.05) for treatment T2. Treatment T2 significantly increased villi height and treatment T5 significantly increased villi thickness in the jejunum, in comparison to the other treatments. In the ileum, treatment T2 resulted in significantly greater increases in villi height, treatment T6 in villi thickness, and treatment T4 in crypt depth compared to the other treatments. In the duodenum and jejunum, there were no statistically significant variations in the numbers of E. coli and Lactobacilli bacteria, but in the ileum, the number of E. coli increased significantly in treatments T3 and T4. In this respect, lactobacilli did not differ noticeably. >
Keywords: Lactobacilli; Chicken; Ileum; Duodenum